Enhancing the Enforcement Powers of ICAO in Aviation Safety and Security - Aquilina, Saviour (Teisė, 2024)
The objective of this article is to determine the improvements required by ICAO’s institutional mechanisms so to enforce compliance with Standards contained in Annexes to the Chicago Convention, detailing preventive safety or security measures. To offer a comprehensive study, the article analyses the enforcement measures under international law, the enforcement mechanisms of organising it internationally, the monitoring mechanisms of ICAO, and the mechanism on the settlement of disputes included in the Chicago Convention. The article recommends a number of amendments to the Chicago Convention and analyses the challenges to achieve such recommendations.